Community radio stations and the issue of social cohesion in Côte d'Ivoire (Cahiers Africains de rhétorique, 2025)
After a violent post-electoral crisis in 2010 which caused more than 3,000 deaths, according to the official report, Côte d'Ivoire is recovering from the traumas of its recent history. More than ten years after the war, the mechanisms of public life continue to be put in place gradually in a context of painful national reconciliation made even more complex with the trial coupled with the International Criminal Court in The Hague of the former head of the State, Laurent Gbagbo and his foal, Mr. Charles Blé Goudé. In this fragile social context, the media, formerly accused of having contributed to setting the country ablaze, are now called upon to participate in the reconstruction of the social fabric. This is particularly the case for local radio stations. How do these local media contribute to strengthening social cohesion in Côte d'Ivoire? This article aims to analyze the role of community media in peacebuilding in Côte d'Ivoire. The documentary study and the individual interviews of some managers of local radios, made it possible to show the important role of local radios in the reconstitution of the social fabric in Côte d'Ivoire. Gatekeeping and agenda setting theories have helped to understand the power of local radios in social relations in Côte d'Ivoire.TRANSLATE with x EnglishArabicHebrewPolishBulgarianHindiPortugueseCatalanHmong DawRomanianChinese SimplifiedHungarianRussianChinese TraditionalIndonesianSlovakCzechItalianSlovenianDanishJapaneseSpanishDutchKlingonSwedishEnglishKoreanThaiEstonianLatvianTurkishFinnishLithuanianUkrainianFrenchMalayUrduGermanMalteseVietnameseGreekNorwegianWelshHaitian CreolePersian  TRANSLATE with COPY THE URL BELOW Back EMBED THE SNIPPET BELOW IN YOUR SITE Enable collaborative features and customize widget: Bing Webmaster PortalBack